Anyám levelei Sztálin elvtárshoz - Mészáros, Márta (Hungary : Cameofilm, 2015)
Márta Mészáros' father, the sculptor László Mészáros, was executed during the Stalinist purges of the Soviet Union. The director addressed her father's fate in many of her earlier films, but this time, she focuses on her mother, Vilma Kovács. Vilma followed her husband to Soviet Kirgizia, and once László was arrested, she was left alone with her children. Vilma's letters are not only documents remembering the terrible times but also a reminder of her struggle as a strong, brave woman who remained faithful to her husband. The letters reveal how the authorities avoided responsibility for their crimes, and expose to what extent human life was worthless during the 1930's Soviet Union. The film is also a story of love and faithfulness and offers glimpses into the life of modern Kyrgyzstan.
Verzio Film Festival Submission
Keywords: Documentary films